Business simulators and lecturer’s perception! The case of University of Algarve - Kikot, Tatiana (2014)
The purpose of this paper is to investigate the usage of simulation/serious games in the University of Algarve (Portugal), because these novel learning environments are still on an early stage of adoption. Members of the Faculty of Economics (in a total 60 lecturers and their assistants) participated in this study through a mixed survey (closed and ask for agreement queries). The empirical evidences denote interesting results: (i) a response rate of 43 percent; (ii) these tools increase learning engagement; (iii) the lack of information and not sufficient alignment with the course unit hinders the uptake of these technologies within classrooms; (iv) lecturers have a positive perception and consider them as valuable for students’ better learning. Hence, this survey provides a good platform for future research and approaches how to promote a better exploration of simulation/serious games and their integration into course curriculum. To conclude, this paper will be divided into five sections: (i) research statement; (ii) research design (aims/objectives, research methodology and data collection/analysis); (iii) findings (lecturers’ profile, awareness, experiences and results summary); (iv) limitations and future work (methodological limitations and tools/ analysis upgrade); and, (v) conclusions.